Infinite language hierarchy based on regular regulated right linear grammars with start strings - Meduna, Alexander (Philippine computing journal)
The present paper discusses regular regulated right-linear grammars with start strings rather than single symbols. It demonstrates that these grammars with start strings consisting of no more than n + 1 symbols are stronger than these grammars with start strings consisting of no more than n symbols, for all n >= 1. On the other hand, these grammars with start strings of any length only generate the family of regular languages if they change the position of rewriting finitely many times during the derivation of any sentence from the generated language.